A negative electrode sheet and a lithium battery using the same
Patent Information
- Application Number
- CN202611140336.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-09
AI Technical Summary
然而,该方案在实际应用中仍存在不足:一方面,活性物质层减薄会直接导致电芯能量密度降低,影响产品竞争力;另一方面,该方案对褶皱改善的效果有限,难以从根源上解决形变匹配问题,且减薄工艺需要对涂布设备进行改造,老旧产线适配难度大、改造成本高,限制了该方案在行业内的推广应用
[0005]为了解决现有技术中的技术问题,本申请提供一种负极极片及应用其的锂电池。
Smart Images

Figure CN122889693A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium battery technology, and in particular to a negative electrode sheet and a lithium battery using the same. Background Technology
[0002] "Octopus wrinkling" on the negative electrode of lithium-ion cells is a typical defect in the production of wound / stacked cells. It manifests as irregular radial wrinkles along the edges of the inner and outer rings of the negative electrode sheet, which seriously affects the pass rate of cell products and long-term reliability.
[0003] Currently, the mainstream solutions in the industry to address this defect, besides the high-investment formation, capacity, and constraint processes, involve thinning the active material layer. This involves reducing the thickness of the active material layer at the edge of the negative electrode to alleviate wrinkles. However, this solution still has shortcomings in practical applications: on the one hand, thinning the active material layer directly leads to a decrease in the cell's energy density, affecting product competitiveness; on the other hand, this solution has limited effectiveness in improving wrinkles, failing to address the deformation matching problem at its root. Furthermore, the thinning process requires modifications to the coating equipment, making adaptation difficult and costly for older production lines, thus limiting the widespread application of this solution in the industry.
[0004] Therefore, how to suppress the octopus-like wrinkling defect of the negative electrode sheet from the root cause without reducing energy density or increasing production line modification costs is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] In order to solve the technical problems in the prior art, this application provides a negative electrode sheet and a lithium battery using the same.
[0006] In a first aspect, this application provides a negative electrode sheet, which adopts the following technical solution: A negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface along the thickness direction of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and a binder. Along the width direction of the negative electrode sheet, the negative electrode sheet includes two edge regions located on both sides and a central region located between the two edge regions, and the sum of the widths of the central region and the two edge regions is equal to the width of the negative electrode sheet. The thickness of the negative electrode active material layer in the central region is the same as the thickness of the negative electrode active material layer in the edge regions. The thickness of the negative electrode current collector in the central region is h1 mm, and the thickness of the negative electrode current collector in the edge regions is h2 mm, where h1 and h2 satisfy h1 > h2. The width of any one of the edge regions of the negative electrode sheet is λ mm. The coefficient of thermal expansion of the negative electrode active material is k, the performance constant of the binder is c, and the mass percentage of the binder in the negative electrode active material layer in the central region is a1. wt%, where the mass percentage of the adhesive in the negative electrode active material layer in the edge region is a2 wt%, and k, λ, c, h1, and a1 satisfy 1.3×(k×λ) / c≤1000×h1 / a1, and k, λ, c, h2, and a2 satisfy 1000×h2 / a2≤28×(k×λ) / c.
[0007] The negative electrode sheet provided in this application achieves synergistic optimization of the deformation adaptability of the central and edge regions through the comprehensive application of current collector partition thickness design, uniform thickness setting of the active material layer throughout, and formulas. During charging and discharging, the negative electrode active material undergoes lithium intercalation volume expansion. This deformation is non-uniformly distributed along the width of the electrode sheet. The central region experiences uniform stress and relies on the mechanical suppression force of the current collector to resist the expansion of the active material. The edge region experiences concentrated stress and relies on the buffering capacity of the binder to absorb the deformation load. This application incorporates the edge region width, the expansion coefficient of the negative electrode active material, and the binder performance constant into a unified framework with the current collector thickness and binder content, ensuring that these parameters satisfy the central region inequality 1.3×(k×λ) / c≤1000×h1 / a1 and the edge region inequality 1000×h2 / a2≤28×(k×λ) / c. Specifically, the central region inequality limits the lower limit of its relative stiffness (1000×h1 / a1). If the relative stiffness of the central region is lower than this lower limit threshold, it means that the thickness of the current collector central region is too thin or the binder content is too low. The central region cannot provide sufficient rigid support to resist the deformation caused by the lithium insertion expansion of the active material. The center of the electrode is prone to concavity and wrinkling deformation, which in turn leads to the risk of lithium plating due to uneven deformation. The edge region inequality limits the upper limit of its relative stiffness (1000×h2 / a2). If the relative stiffness of the edge region is higher than this upper limit threshold, it means that the thickness of the current collector edge region is too thick or the binder content is too low. The edge region cannot maintain appropriate flexibility to complete the lithium insertion deformation synchronously with the active layer. Excessive edge stiffness leads to deformation accumulation, which in turn causes the active layer to debond, material to fall off, and electrode edge wrinkling.
[0008] The synergistic effect of the two aforementioned inequalities ensures the stability of the gradient structure—with rigid support in the central region and flexible buffering in the edge region—during charge-discharge cycles. The rigid support in the central region effectively resists lithium intercalation expansion deformation, while the flexible buffering in the edge region effectively absorbs deformation loads and releases deformation stress. This synergistic effect fundamentally suppresses the "octopus-like" wrinkling defect. Simultaneously, the uniform thickness of the active material layer across the entire surface ensures consistent active material loading in both the central and edge regions, preventing a decrease in cell energy density due to localized thinning. Furthermore, this design eliminates the need to adjust the coating thickness gradient or modify the coating process, allowing direct adaptation to existing equipment in slurry preparation, coating, die-cutting, and rolling processes on existing production lines. This eliminates the need for additional large-scale production equipment, significantly reducing production line modification costs and process debugging difficulties. It overcomes the technical problems of limited improvement effects, reduced energy density, and difficulty in adapting to existing production lines associated with existing active material layer thinning solutions.
[0009] Preferably, 1.3×(k×λ) / c≤1000×h1 / a1≤28×(k×λ) / c, and / or, 1.3×(k×λ) / c≤1000×h2 / a2≤28×(k×λ) / c.
[0010] Preferably, 1.5×(k×λ) / c≤1000×h1 / a1≤27×(k×λ) / c, and / or, 1.5×(k×λ) / c≤1000×h2 / a2≤27×(k×λ) / c.
[0011] Preferably, the value of h1 is 0.006-0.008, and / or the value of h2 is 0.004-0.006.
[0012] Preferably, a1 and a2 satisfy at least one of the following conditions: (a) a1 = 0.5-3.0; (b) a2 = 2.0-5.0; (c) a2 > a1.
[0013] Preferably, k, λ, and c satisfy at least one of the following conditions: (1) the value of k is 5%-250%; (2) the value of λ is 1-5; (3) the value of c is 0.8-1.2.
[0014] Preferably, the thickness of the negative electrode sheet is 50-200 μm.
[0015] Secondly, this application provides a lithium battery, which adopts the following technical solution: A lithium battery includes a positive electrode, a separator, an electrolyte, and a negative electrode as described above.
[0016] Preferably, the difference in width between one side of the negative electrode and the positive electrode is less than the width of any of the edge regions and less than the difference in width between one side of the separator and the negative electrode.
[0017] Preferably, the ratio of the thickness of the positive electrode to the thickness of the negative electrode is 0.6-1.2. Attached Figure Description
[0018] Figure 1 This is a photograph of the surface state of the negative electrode sheet after disassembly of the lithium battery provided in Embodiment 1 of this application.
[0019] Figure 2 This is a photograph of the surface state of the negative electrode sheet after disassembly of the lithium battery provided in Comparative Example 1 of this application. Detailed Implementation
[0020] To better understand and implement this application, the technical solutions of this application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only some of the embodiments of this application, and not all of them.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application.
[0022] Unless otherwise stated, all numerical values for the amounts of expressed components, reaction conditions, etc., used in the specification and claims are to be understood as being modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth herein are approximate values that can be varied to obtain the desired performance.
[0023] Unless otherwise stated, the terms “a,” “an,” “an,” and “the” as used in this specification are intended to include “at least one” or “one or more.” For example, “a component” refers to one or more components, and therefore more than one component may be considered and may be employed or used in the implementation of the described embodiments.
[0024] The word “and / or” as used in this article refers to one or all of the elements mentioned.
[0025] The terms "include" and "contain" as used in this article cover both cases where only the mentioned elements exist and cases where other unmentioned elements exist in addition to the mentioned elements.
[0026] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0027] A first aspect of this application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface along the thickness direction of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material and a binder; along the width direction of the negative electrode sheet, the negative electrode sheet includes two edge regions located on both sides and a central region located between the two edge regions, and the sum of the widths of the central region and the two edge regions is equal to the width of the negative electrode sheet; the thickness of the negative electrode active material layer in the central region is the same as the thickness of the negative electrode active material layer in the edge regions; the thickness of the negative electrode current collector in the central region is h1 mm, and the thickness of the negative electrode current collector in the edge regions is h2 mm, wherein h1 and h2 satisfy h1 > h2; the width of any one of the edge regions of the negative electrode sheet is λ mm; the coefficient of thermal expansion of the negative electrode active material is k, the performance constant of the binder is c, and the mass percentage of the binder in the negative electrode active material layer in the central region is a1. The mass percentage of the adhesive in the negative electrode active material layer in the edge region is a2 wt%. The values of k, λ, c, h1, and a1 satisfy 1.3×(k×λ) / c ≤ 1000×h1 / a1, and k, λ, c, h2, and a2 satisfy 1000×h2 / a2 ≤ 28×(k×λ) / c. For example, the values of k, λ, c, h1, and a1 satisfy any one of the following correspondences: 1.3×(k×λ) / c ≤ 900×h1 / a1, 1.3×(k×λ) / c ≤ 800×h1 / a1, 1.3×(k×λ) / c ≤ 500×h1 / a1, 1.3×(k×λ) / c ≤ 200×h1 / a1, or any one of the ranges formed by any pairwise correspondences mentioned above. For example, the k, the λ, the c, the h2, and the a2 satisfy any one of the following correspondences: 1000×h2 / a2≤28×(k×λ) / c, 1000×h2 / a2≤20×(k×λ) / c, 1000×h2 / a2≤10×(k×λ) / c, 1000×h2 / a2≤5×(k×λ) / c, or any one of the above pairwise correspondences within a range of values.
[0028] In one embodiment of this application, the expansion coefficient k of the negative electrode active material refers to the relative volume expansion ratio of the negative electrode active material in a fully lithium-intercalated (fully charged) state.
[0029] In one embodiment of this application, the adhesive performance constant c is a dimensionless parameter characterizing the interfacial bonding strength and stress buffering capacity of the adhesive. It is determined through a peel strength test: first, the peel strength P (in N / mm) of the adhesive system under test on a standard negative electrode sheet is measured using the 180° peel method. The peel strength is defined as the ratio of the average peel force F to the electrode width W. Then, the ratio of the peel strength P of the adhesive under test to the peel strength P0 of the reference adhesive system is defined as c, i.e., c = P / P0. In this application, the reference adhesive system uses the peel strength of the standard SBR+CMC system on a conventional graphite electrode sheet, with P0 set to 0.15 N / mm. A larger c value indicates higher interfacial bonding strength and stronger stress buffering capacity of the adhesive. This definition allows the performance differences between different adhesive systems to be quantitatively expressed through the dimensionless constant c, thus enabling them to be uniformly incorporated into the formulas of this application for calculation.
[0030] In one embodiment of this application, the negative electrode active material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, silicon-oxygen materials, and silicon-carbon composite materials; the binder includes at least one of styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyimide (PI), polyvinylidene fluoride (PVDF), and waterborne polyurethane (PAA).
[0031] In one embodiment of this application, the negative electrode active material layer further includes a conductive agent, which includes at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, graphene, and conductive graphite.
[0032] In one embodiment of this application, 1.3×(k×λ) / c≤1000×h1 / a1≤28×(k×λ) / c, and / or, 1.3×(k×λ) / c≤1000×h2 / a2≤28×(k×λ) / c. Exemplarily, the k, λ, c, h1, and a1 satisfy any one of the following correspondences: 1.3×(k×λ) / c≤1000×h1 / a1≤28×(k×λ) / c, 1.5×(k×λ) / c≤1000×h1 / a1≤25×(k×λ) / c, 1.8×(k×λ) / c≤1000×h1 / a1≤20×(k×λ) / c, or any one of the ranges formed by any pairwise correspondences of the above. For example, the k, the λ, the c, the h2, and the a2 satisfy any one of the following correspondences: 1.3×(k×λ) / c≤1000×h2 / a2≤28×(k×λ) / c, 1.8×(k×λ) / c≤1000×h2 / a2≤20×(k×λ) / c, 2.2×(k×λ) / c≤1000×h2 / a2≤15×(k×λ) / c, or any one of the above pairwise correspondences within a range of values. By further requiring the relative stiffness of the central region to be no higher than the upper threshold and the relative stiffness of the edge region to be no lower than the lower threshold, the relative stiffness of both the central and edge regions is kept within a complete range defined by the lower and upper limits. This ensures that the rigid support strength of the central region and the flexible buffering capacity of the edge region are in optimal balance, preventing deformation from concentrating and shifting to the edge due to excessive relative stiffness in the central region, or insufficient structural strength in the edge region due to insufficient relative stiffness, thus failing to provide effective support for the active material. This further optimizes the overall deformation adaptability of the electrode. If the relative stiffness of the central region exceeds the upper threshold, it means that the current collector is too thick or the binder content is too low, resulting in high overall electrode rigidity, enhanced internal constraint, and deformation shifting to the edge, which in turn exacerbates the accumulation of deformation at the edge. If the relative stiffness of the edge region is lower than the lower threshold, it means that the current collector is too thin or the binder content is too high, resulting in insufficient structural strength in the edge region, failing to provide necessary support for the active material, and making it prone to deformation instability during charge-discharge cycles.
[0033] In one embodiment of this application, 1.5×(k×λ) / c≤1000×h1 / a1≤27×(k×λ) / c, and / or, 1.5×(k×λ) / c≤1000×h2 / a2≤27×(k×λ) / c. Exemplarily, the k, λ, c, h1, and a1 satisfy any one of the following correspondences: 1.5×(k×λ) / c≤1000×h1 / a1≤27×(k×λ) / c, 2.0×(k×λ) / c≤1000×h1 / a1≤18×(k×λ) / c, 2.5×(k×λ) / c≤1000×h1 / a1≤13×(k×λ) / c, or any one of the ranges formed by any pairwise correspondences of the above. For example, the k, the λ, the c, the h2, and the a2 satisfy any one of the following correspondences: 1.5×(k×λ) / c≤1000×h2 / a2≤27×(k×λ) / c, 1.9×(k×λ) / c≤1000×h2 / a2≤18×(k×λ) / c, 2.5×(k×λ) / c≤1000×h2 / a2≤13×(k×λ) / c, or any one of the above pairwise correspondences within a range of values.
[0034] In one embodiment of this application, the value of h1 is 0.006-0.008, and / or the value of h2 is 0.004-0.006. Exemplarily, the value of h1 is any one of 0.006, 0.007, 0.008, or any value within the range formed by any two of the above values; the value of h2 is any one of 0.004, 0.005, 0.006, or any value within the range formed by any two of the above values. This gradually narrowing matching window means a more precise match between the ratio of current collector thickness to adhesive content and the material expansion characteristics, edge region width, and adhesive performance. Under the condition of meeting a more stringent matching window, the relative stiffness of the central region and the edge region is limited to a narrower optimal range. The coordination between the rigid support capacity of the central region and the flexible buffer capacity of the edge region is more precise. The uniformity of the deformation distribution of the entire electrode is further improved, the suppression effect of octopus wrinkling is further optimized, and the structural stability of the electrode is further enhanced, effectively reducing the risk of active material debonding, material loss and electrode edge cracking.
[0035] In one embodiment of this application, a1 and a2 satisfy at least one of the following conditions: (a) a1 = 0.5-3.0; (b) a2 = 2.0-5.0; (c) a2 > a1. For example, the value of a1 is any one of 0.5, 0.8, 1.5, 2.2, 2.6, 3.0, or any value within the range formed by any two of the above values; the value of a2 is any one of 2.0, 2.6, 3.0, 3.6, 4.0, 4.6, 5.0, or any value within the range formed by any two of the above values. The binder plays a role in bonding the active material particles and the interface between the active material layer and the current collector in the negative electrode active material layer. Its content directly affects the cohesion, interfacial bonding strength, and flexible buffering capacity of the electrode. The binder content in the central region is controlled within the aforementioned lower range to avoid increased internal resistance and decreased active material content due to excessive binder content, while ensuring moderate interfacial bonding strength in the central region to maintain structural stability. The binder content in the edge region is controlled within the aforementioned higher range, satisfying a2 > a1, allowing for higher binder content in the edge region to enhance interfacial bonding strength and flexible buffering capacity, thereby effectively coping with higher deformation loads in the edge region. Through this zoned binder content control, the central region maintains a high active material content and low internal resistance with a lower binder content, while the edge region maintains interfacial bonding strength and deformation buffering capacity with a higher binder content, ensuring the electrode maintains structural integrity and deformation adaptability during charge-discharge cycles.
[0036] In one embodiment of this application, k, λ, and c satisfy at least one of the following conditions: (1) the value of k is 5%-250%; (2) the value of λ is 1-5; (3) the value of c is 0.8-1.2. For example, the value of k is any one of 5%, 20%, 50%, 100%, 200%, 250%, or any value within the range of any two of the above values; the value of λ is any one of 1, 2, 2.5, 3, 4, 5, or any value within the range of any two of the above values; the value of c is any one of 0.8, 0.9, 1, 1.1, 1.2, or any value within the range of any two of the above values.
[0037] In one embodiment of this application, when the negative electrode active material is a silicon-containing negative electrode material, the expansion coefficient k is 200%-240%. For example, the value of k is any one of 200%, 210%, 220%, 230%, 240%, 250%, or any value within the range of any two of the above values.
[0038] In one embodiment of this application, the value of λ is 1-2. For example, the value of λ is any value from 1, 1.2, 1.4, 1.6, 1.8, 2 or any value within the range of any two of the above values.
[0039] In one embodiment of this application, the value of λ in the laminated cell is between 1.4 and 2; exemplarily, the value of λ is any value from 1.4, 1.5, 1.6, 1.8, 1.9, 2, or any value within the range formed by any pair of the above values. In the wound cell, the value of λ is between 1 and 1.4; exemplarily, the value of λ is any value from 1, 1.1, 1.2, 1.3, 1.4, or any value within the range formed by any pair of the above values.
[0040] The three parameters mentioned above collectively determine the lower threshold of the relative stiffness of the central region and the upper threshold of the relative stiffness of the edge region in the formula. The value of k reflects the severity of lithium intercalation expansion of the negative electrode active material, covering a wide range of materials from low-expansion graphite systems (k approximately 10%) to high-expansion silicon-carbon systems (k approximately 150%-200%), enabling this application to adapt to negative electrode active materials with different expansion characteristics. The value of λ reflects the actual width of the edge region, covering different degrees of edge deformation aggregation under winding and stacking processes, enabling this application to adapt to different cell forming methods. The value of c reflects the strength of the binder interface buffering capacity, covering the performance differences of different types of binders, enabling this application to adapt to different binder systems. The limitation of the value range of the above three parameters ensures that the formula of this application remains effective under a wide range of material systems and process conditions, possessing good process universality and material compatibility.
[0041] In one embodiment of this application, the thickness of the negative electrode sheet is 50-200 μm. Exemplarily, the thickness of the negative electrode sheet is any value selected from 50 μm, 70 μm, 100 μm, 130 μm, 180 μm, and 200 μm, or any value within the range formed by any two of the above values. The total thickness of the negative electrode sheet directly affects the length of the lithium-ion transport path in the active material layer, the structural rigidity of the electrode sheet, and the energy density of the battery cell. Controlling the total thickness of the negative electrode sheet within the above range ensures that the ion transport path remains at a reasonable length, avoiding increased polarization and deterioration of fast-charging performance due to excessive electrode thickness, while also avoiding low energy density and insufficient structural rigidity due to excessively thin electrode sheets. Within this thickness range, the electrode sheet possesses sufficient structural rigidity to resist lithium intercalation expansion deformation, while maintaining appropriate flexibility to adapt to the forming requirements of winding or stacking processes. This allows the current collector partition thickness design and the equal thickness setting of the active material layer in this application to fully utilize the deformation adaptation effect on an electrode sheet with a good structural foundation.
[0042] A second aspect of this application provides a lithium battery, including a positive electrode, a separator, an electrolyte, and a negative electrode as described above.
[0043] In one embodiment of this application, the difference in width between one side of the negative electrode and the positive electrode is less than the width of any of the edge regions and less than the difference in width between one side of the separator and the negative electrode.
[0044] In one embodiment of this application, the difference in width between the negative electrode and the positive electrode refers to the width of the negative electrode exceeding the width of the positive electrode on one side when the negative electrode and the positive electrode are arranged at the same center, i.e., (width of negative electrode - width of positive electrode) / 2; correspondingly, the difference in width between the separator and the negative electrode refers to the width of the separator exceeding the width of the negative electrode on one side when they are arranged at the same center, i.e., (width of separator - width of negative electrode) / 2.
[0045] The edge of the positive electrode sheet must fall within the edge region of the negative electrode sheet. This ensures that the high-deformation region corresponding to the edge of the positive electrode sheet matches the deformation buffer structure of the negative electrode sheet edge region. This guarantees that lithium-ion insertion and extraction at the edge of the positive electrode sheet occur within the edge region of the negative electrode sheet, which has a high binder content and moderate flexibility, preventing localized stress concentration caused by the positive electrode sheet edge corresponding to the center region of the negative electrode sheet. Simultaneously, the edge region of the negative electrode sheet must be completely covered by the separator, meaning the width of the edge region is less than the difference in width between the separator and the single side of the negative electrode sheet. This allows the separator to cover the edge of the negative electrode sheet, preventing the edge from exceeding the separator's coverage and causing internal short circuit risks. Through these dual boundary constraints, the width of the negative electrode sheet edge region is designed to meet both the dimensional requirements for cell structural safety and the design requirements for uniform deformation across the entire area, while ensuring that the edge of the positive electrode sheet falls within the edge region and the edge of the negative electrode sheet does not exceed the separator's coverage.
[0046] In one embodiment of this application, the ratio of the thickness of the positive electrode to the thickness of the negative electrode is 0.6-1.2. Exemplarily, the ratio of the thickness of the positive electrode to the thickness of the negative electrode can be any value from 0.6, 0.7, 0.8, 0.9, 1.1, 1.2, or any ratio within the range formed by any pair of the above ratios. Both the positive and negative electrodes undergo lithium insertion / deintercalation volume changes during charging and discharging; the thickness ratio of the two determines the synergy of the overall deformation behavior of the battery cell. When the ratio of the thickness of the positive electrode to the thickness of the negative electrode is within the above range, the expansion and contraction behaviors of the positive and negative electrodes are within a matching range. This allows the deformation of the positive and negative electrodes along the thickness direction to be coordinated and synchronized during charge and discharge cycles. This avoids the problem of uneven stress on the edge of the negative electrode being aggravated by the expansion and contraction behavior of the positive electrode becoming the dominant factor in the cell deformation due to excessive thickness. At the same time, it avoids the risk of edge deformation due to excessive load on the negative electrode caused by excessively thin positive electrode. This further optimizes the uniformity of the global deformation distribution at the cell level. Together with the current collector partition thickness design and formula of the negative electrode itself, it improves the cycle stability and structural reliability of the cell.
[0047] In one embodiment of this application, the thickness of the separator is 5-20 μm. Exemplarily, the separator thickness is any value selected from 5 μm, 7 μm, 10 μm, 13 μm, 18 μm, and 20 μm, or any value within a range formed by any two of these values. Within this range, the separator possesses moderate rigidity to maintain good adhesion to the electrode surface, avoiding uneven edge constraint and deformation concentration caused by excessive rigidity. Simultaneously, it possesses sufficient mechanical strength to resist the stress generated by the expansion and contraction of the electrode during winding and cycling, preventing separator deformation or wrinkles from disrupting the deformation distribution balance at the electrode edge, and ensuring effective isolation between the positive and negative electrodes to reduce the risk of internal short circuits. This thickness setting ensures that the separator, while maintaining mechanical isolation, does not impose additional constraints on the flexible buffer mechanism of the negative electrode edge region, ensuring that the edge region can deform synchronously with the active layer, maintaining the uniformity of the deformation distribution across the entire electrode area. When the diaphragm thickness is too large, the diaphragm rigidity is too high, resulting in poor adhesion to the electrode and uneven edge constraint, while the ion conduction resistance increases. When the diaphragm thickness is too small, the mechanical strength of the diaphragm is insufficient, and it is easy to deform and wrinkle during winding or cycling, which will disrupt the balance of electrode edge deformation distribution and increase the risk of internal short circuit.
[0048] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0049] Example 1 1. Preparation of positive electrode sheet A nickel-cobalt-manganese ternary cathode active material, conductive agent Super P, and binder PVDF were mixed at a mass ratio of 97:1.5:1.5. N-methylpyrrolidone solvent was added, and the mixture was stirred evenly in a vacuum mixer to prepare a cathode slurry. The cathode slurry was uniformly coated onto both sides of an aluminum foil, and after drying, rolling, and slitting, a cathode sheet with a total thickness of 100 μm was obtained. The slitted cathode sheet was fitted with aluminum cathode tabs, which were connected to the cathode current collector by welding.
[0050] 2. Preparation of negative electrode sheet A silicon-carbon composite anode active material (18% silicon content and 82% natural graphite content, with an expansion coefficient k of 1.20), conductive agent acetylene black, and binder polyacrylic acid (with a performance constant c of 1.00) are mixed in a mass ratio of 96.75:1.5:1.75, and deionized water solvent is added. The mixture is stirred evenly in a vacuum mixer to prepare anode slurry one. Silicon-carbon composite anode active material (silicon content 18% and natural graphite content 82%, expansion coefficient k of anode active material is 1.20), conductive agent acetylene black, binder polyacrylic acid (binder performance constant c is 1.00) are mixed in a mass ratio of 95:1.5:3.5, deionized water solvent is added, and the mixture is stirred evenly in a vacuum mixer to prepare anode slurry II.
[0051] An electrolytic copper foil is provided as the negative electrode current collector. The current collector is divided into a central region and two edge regions located on both sides of the central region along its width. The width of the central region is 97 mm, and the width of each of the two edge regions is 1.5 mm (λ). The thickness (h1) of the current collector in the central region is 0.007 mm, and the thickness (h2) of the current collector in each of the two edge regions is 0.005 mm.
[0052] The first negative electrode slurry was uniformly coated onto the central region of both sides of the current collector, and the second negative electrode slurry was uniformly coated onto the edge regions of both sides of the current collector. After drying, the coating was rolled and slit to obtain the negative electrode sheet. During the coating process, the thickness of the active material layer in the central region and the edge region remained consistent, and the total thickness of the negative electrode sheet was 125 μm. The mass percentage (a1 wt%) of the binder in the negative electrode active material layer in the central region was 1.75 wt%, and the mass percentage (a2 wt%) of the binder in the negative electrode active material layer in the edge region was 3.50 wt%. The slit negative electrode sheet was equipped with negative electrode tabs, which were die-cut from the empty foil area at the edge of the current collector. The difference in width between the negative electrode sheet and the positive electrode sheet on one side was 1 mm.
[0053] 3. Diaphragm A 12.5μm thick polypropylene porous membrane with a width of 108mm was selected, and the difference in width between the membrane and the negative electrode plate on one side was 4mm.
[0054] 4. Lithium battery assembly The positive electrode, separator, and negative electrode are stacked in sequence, with the edge of the positive electrode falling within the edge area of the negative electrode. The positive and negative electrodes are aligned and centered, and then wound to form an electrode assembly. The electrode assembly is placed in a packaging shell, electrolyte is injected, and after processes such as encapsulation, settling, formation, and aging, a lithium battery is obtained.
[0055] The configuration of the negative electrode in Examples 1-11 and Comparative Examples 1-3 is shown in Table 1. Except for the parameters listed in Table 1, the other parameter settings and preparation processes of Examples 2-13 and Comparative Examples 1-3 are consistent with those of Example 1.
[0056] Table 1
[0057] Specifically, in Example 6 of Table 1, the binder was replaced with waterborne polyurethane; in Example 7, the negative electrode active material was replaced with a silicon-carbon composite negative electrode active material with a silicon content of 10% and an artificial graphite content of 90%; and in Example 8, the negative electrode active material was replaced with a silicon-carbon composite negative electrode active material with a silicon content of 25% and a hard carbon content of 75%.
[0058] It should be noted that in the embodiments and comparative examples in Table 1, when adjusting the binder content a1 and a2, the amount of negative electrode active material was adjusted accordingly to maintain a balance. That is, when the binder content increases, the amount of negative electrode active material is reduced accordingly, and when the binder content decreases, the amount of negative electrode active material is increased accordingly, so as to keep the conductive agent content and slurry solid content constant.
[0059] The configuration of the positive and negative electrode plates in Examples 1 and 14-19 is shown in Table 2. Except for the parameters listed in Table 2, the other parameter settings and preparation processes of Examples 14-19 are consistent with those of Example 1.
[0060] Table 2
[0061] Test methods I. k-value test Take the negative electrode active material to be tested, and mix it with binder and conductive agent at a mass ratio of 95:3:2 (negative electrode active material: binder SBR / CMC: conductive agent Super P). Add deionized water solvent and stir evenly in a vacuum mixer to prepare a negative electrode slurry. Coat the negative electrode slurry onto the surface of a copper foil current collector, and after drying, rolling, and slitting, prepare negative electrode sheets. Punch the above electrode sheets into circular pieces with a diameter of 12-16 mm, and assemble them into coin cell half-cells using lithium metal as the counter electrode.
[0062] Before assembling the coin cell, measure the total thickness H0 of the original electrode and the thickness t of the copper foil current collector, and calculate the original active material layer thickness h0 = H0 - t. During measurement, five points are evenly selected on the electrode surface (one point in the center and one point on each of the four edges), and the arithmetic mean is taken.
[0063] The coin cell was discharged at a constant temperature of 25°C with a current of 0.1C to 0.005V (lithium intercalation, corresponding to a fully charged state) to ensure complete lithium intercalation in the negative electrode active material. The coin cell was disassembled in an inert atmosphere glove box, the negative electrode was removed, cleaned with dimethyl carbonate (DMC) to remove residual electrolyte, and dried. The total thickness H1 of the fully charged electrode was measured, and the thickness of the fully charged active material layer h1 = H1 - t (the copper foil thickness t remained constant). Five points were uniformly selected on the electrode surface during measurement, and the arithmetic mean was taken.
[0064] The expansion coefficient k is calculated using the following formula: k = h1 / h0 × 100%; For each negative electrode active material, at least three parallel samples were tested, and the arithmetic mean was taken as the k value of the material.
[0065] II. λ value test After completing a charge-discharge cycle, the battery cell is disassembled to obtain the negative electrode. The negative electrode is flattened and placed on an optical measurement platform. Using a tool microscope or CCD image measuring instrument, the actual width of the edge regions on both sides of the electrode is measured along its width direction. The width of any edge region is the distance extending from the side of the electrode towards the center to the boundary of the fully coated area on the surface of the active material layer. Five measurement positions are evenly selected along the length of the electrode, and the width of the edge regions on both sides is measured. The arithmetic mean of all measurements is taken as the λ value, with a measurement accuracy of 0.01 mm.
[0066] If the cell has a wound structure, the width of the edge area corresponding to the inner and outer rings of the electrode after winding needs to be measured separately, and the larger value is taken as the λ value of the cell; if the cell has a stacked structure, the arithmetic mean of the edge area widths of the multiple electrode layers is taken as the λ value of the cell.
[0067] III. c-value test The adhesive performance constant c is calculated using the following formula: c = P / P0; Wherein, P0 is the peel strength of the reference adhesive system. In this application, the reference adhesive system adopts the peel strength of the standard SBR+CMC system under conventional graphite electrodes, and the value of P0 is 0.15 N / mm. P is the peel strength, which is calculated using the following formula: P=F / W; Where F is the average peeling force (in N), W is the width of the negative electrode (in mm), and P is in N / mm.
[0068] The test method for average peel force F is as follows: The adhesive system to be tested is mixed with the negative electrode active material and conductive agent according to the actual formula to prepare a negative electrode slurry. This slurry is coated onto the surface of a copper foil current collector, dried, and rolled to form a negative electrode sheet. The electrode sheet is cut into samples with a width W of 20 mm, and tested using the 180° peel method: The active material layer of the sample is placed face down and adhered to a rigid steel plate with double-sided tape. The steel plate is fixed in the lower fixture of a universal testing machine. One end of the electrode sheet is bent upwards at a 180° angle and clamped in the upper fixture. A peel test is performed at a tensile speed of 50 mm / min. The force-displacement curve during the peel process is recorded, and the average value of the peel force after it reaches a stable plateau period is taken as the average peel force F.
[0069] For each adhesive system, at least three parallel samples should be tested, and the arithmetic mean should be taken as the c value of the adhesive system.
[0070] IV. h1 and h2 value testing Take the negative electrode sheet to be tested, and cut samples from the central and edge regions along the width direction of the negative electrode sheet. Fix the electrode sheet on the sample stage with the cross-section facing upwards. The sampling position in the central region is at the geometric center along the width direction of the electrode sheet, and the sampling position in the edge region is within 1-3 mm from the side edge along the width direction of the electrode sheet.
[0071] The cross-section was polished using an ion polishing machine to clearly expose the current collector cross-section. The cross-section was observed and photographed using a scanning electron microscope (SEM), and the thickness of the current collector was measured from the images. Five measurement points were evenly selected along the length of the electrode in each region, and the thickness of the current collector at each point was measured. The arithmetic mean was taken as the current collector thickness for that region, with a measurement accuracy of 0.1 μm.
[0072] If the active material layer on both sides of the current collector is coated, the active material layer needs to be removed by soaking in an organic solvent (such as N-methylpyrrolidone or ethyl methyl carbonate) after sampling, or the current collector cross-section can be exposed by ion milling and then measured.
[0073] V. Lithium-ion battery cycle performance test The assembled battery was charged at a constant temperature of 25°C with a constant current and constant voltage of 0.1C to 4.2V, and the cutoff current was 0.05C; then discharged at 0.33C to 2.5V to obtain the discharge capacity of the first cycle. The above steps were repeated for 1000 charge-discharge cycles to obtain the discharge capacity of the 1000th cycle. The capacity retention rate was calculated using the following formula: Capacity retention = Discharge capacity at 1000th cycle / Discharge capacity at the first cycle × 100%.
[0074] After testing, the battery was disassembled in an inert atmosphere glove box, the negative electrode was removed, and the surface residual electrolyte was removed by cleaning with dimethyl carbonate (DMC) and then dried.
[0075] VI. Octopus Wrinkling Defect Rate Test For each set of examples and comparative examples, 30 parallel cells were prepared (with specifications consistent with the capacity test sample, electrode size 100mm×50mm, stacked assembly), and formation was completed according to the same process (0.1C charging to 4.2V, 0.33C discharging to 2.5V).
[0076] Thirty parallel cells were placed in a 25°C environment and subjected to constant current charge-discharge cycles for 50 cycles (the octopus-like wrinkling defect became stable after 50 cycles), with a charge-discharge voltage range of 2.5-4.2V.
[0077] After 50 cycles, disassemble all the cells and observe the edge condition of the negative electrode. The octopus wrinkling defect is judged by obvious wrinkles and lifting at the edge of the electrode, with a wrinkle length ≥2mm and a width ≥0.5mm (consistent with the original disassembly photo judgment standard). The defect rate is calculated using the following formula: Defect rate = (number of cells with octopus-like wrinkles / total number of cells) × 100%, and the statistical results of 30 parallel cells are taken as the final defect rate.
[0078] VII. Active Substance Shedding Rate Test Five qualified electrode sheets (bare electrode sheets without battery cells) were selected for each set of examples and comparative examples. The initial mass m0 of the electrode sheets (including current collector, active material and binder) was weighed using an electronic balance (accuracy 0.1mg).
[0079] The electrode was placed in an expansion environment simulating cell cycling: the electrode was placed in a rigid fixture, a surface pressure of 0.2 MPa was applied, and it was kept at 25°C for 24 hours to simulate the expansion deformation caused by 50 charge-discharge cycles. After removing the electrode, the surface was gently wiped with a lint-free cloth to remove any detached active material particles; the mass of the electrode, m1, was weighed again using an electronic balance, and the mass difference Δm = m0 - m1 was recorded.
[0080] The shedding rate is calculated using the following formula: Shedding rate = Δm / m0 × 100%; Since the mass ratio of current collector and binder is extremely low and can be ignored, Δm is approximately the mass of the detached active material, and the average value of 5 parallel electrodes is taken as the final detachment rate.
[0081] 8. Cell Internal Resistance Test Five qualified battery cells (without wrinkles or lithium plating) were selected for each set of examples and comparative examples. After formation, they were placed in a 25°C temperature-controlled chamber for 2 hours to allow the cell temperature to stabilize.
[0082] An AC impedance meter (model: CHI660E) was used for testing. The test frequency range was 10mHz-100kHz, the AC signal amplitude was 5mV, and the test temperature was 25±0.5℃. The meter probes were connected to the positive and negative terminals of the battery cell, and the AC impedance spectrum of the battery cell was measured using a two-electrode system. The resistance value corresponding to the high-frequency band (10kHz) in the impedance spectrum was read as the internal resistance of the battery cell, in mΩ.
[0083] Each cell was tested three times, and the arithmetic mean of the three test results was taken. The average internal resistance of the five parallel cells was taken as the final internal resistance of the example / comparative example, with a relative standard deviation (RSD) of ≤5%.
[0084] Table 3
[0085] In conjunction with Example 1, Comparative Examples 1-3, and Tables 1 and 3, Figure 1-2 As can be seen, compared with Example 1, Comparative Example 1 adopts a current collector thickness design (h1=h2=0.007mm) and the same binder content in the central and edge regions (a1=a2=2.00wt%). Under the above variable differences, the relative stiffness of Comparative Example 1 is not significantly different in the central and edge regions, and it cannot form a gradient structure of central rigid support and edge flexible buffer. Due to the lack of sufficient flexible buffer capacity in the edge region, the deformation load is concentrated, causing severe octopus wrinkling defects. The defect rate increases from 2.8% in Example 1 to 38.5%. At the same time, the active material shows significant detachment during cycling due to insufficient interfacial bonding force, and the detachment rate increases from 0.65% in Example 1 to 2.15%, resulting in a decrease in capacity retention rate from 92.5% in Example 1 to 89.5%, and an increase in internal resistance from 28.5mΩ to 34.7mΩ. The above results indicate that the synergistic design of current collector partition thickness and binder partition content is the key to constructing a gradient structure and achieving deformation adaptation.
[0086] Compared to Example 1, Comparative Example 2 adopted a current collector thickness design (h1=h2=0.007mm) and the same binder content in the central and edge regions (a1=a2=1.80wt%). However, it employed an active material layer thinning scheme in the edge region, altering the thickness distribution of the edge active material layer. Despite these differences, the edge region of Comparative Example 2 still lacked adequate flexible buffering capacity. Furthermore, the thinning of the active material layer led to a decrease in the active material loading in the edge region, further exacerbating the local overpotential increase and lithium plating risk. Its defect rate increased from 2.8% in Example 1 to 42.1%, capacity retention decreased from 92.5% to 89.2%, the shedding rate increased from 0.65% to 1.82%, and internal resistance increased from 28.5mΩ to 33.9mΩ. These results indicate that simply thinning the active material layer cannot fundamentally solve the deformation matching problem; instead, it may degrade electrochemical performance due to the decreased active material loading.
[0087] Compared with Example 1, Comparative Example 3 reduced the thickness h1 of the current collector in the central region from 0.007 mm to 0.001 mm, while keeping the binder content a1 in the central region unchanged at 1.75 wt%. This resulted in the relative stiffness (1000 × h1 / a1) of the central region decreasing from 4.00 in Example 1 to 0.57, which is lower than the defined lower threshold of 1.3 × (k × λ) / c = 2.34. In other words, the central region does not meet the constraints of the formula of this application. However, the parameters (h2 = 0.005 mm, a2 = 3.50 wt%) and k, λ, and c of the edge region are consistent with those of Example 1, and the edge region still meets the constraints of the formula. Under the aforementioned variable differences, the central region of Comparative Example 3 suffers from insufficient rigidity due to the excessively thin current collector (only 1 μm), failing to effectively resist the deformation caused by the expansion of lithium intercalation in the active material. During charge-discharge cycles, the central region of the electrode experiences concavity and wrinkling due to a lack of sufficient mechanical restraint, leading to severe "octopus-like" wrinkling defects. The defect rate increases from 2.8% in Example 1 to 42.9%. Simultaneously, the deformation instability of the central region causes large-scale shedding of the active material during cycling, with the shedding rate increasing from 0.65% in Example 1 to 2.62%. Capacity retention decreases from 92.5% to 88.1%, and internal resistance increases from 28.5 mΩ to 36.5 mΩ. These results demonstrate that even if the edge region meets the constraints of the formula in this application, if the central region does not meet the formula constraints (i.e., the relative stiffness of the central region is below the lower threshold), it is still impossible to achieve balanced deformation adaptation across the entire electrode region. Deformation failure in the central region directly leads to severe wrinkling defects and performance degradation.
[0088] Based on Examples 1-5 and Tables 1 and 3, it can be seen that compared with Example 1, Examples 2-5 show that in Example 2, h1 and h2 are simultaneously reduced (h1 is reduced from 0.007mm to 0.006mm, and h2 is reduced from 0.005mm to 0.004mm), in Example 3, h1 and h2 are simultaneously increased (h1 is increased from 0.007mm to 0.008mm, and h2 is increased from 0.005mm to 0.006mm), in Example 4, a1 and a2 are simultaneously reduced (a1 is reduced from 1.75wt% to 0.50wt%, and a2 is reduced from 3.50wt% to 2.00wt%), and in Example 5, a1 and a2 are simultaneously increased (a1 is increased from 1.75wt% to 3.00wt%, and a2 is increased from 3.50wt% to 5.00wt%). Under the aforementioned variable adjustments, the defect rates of Examples 1-5 remained at a low level of 2.5%-2.9% without significant fluctuations, indicating that as long as the formula constraints are met, variations in the current collector thickness and adhesive content within their respective preferred ranges have limited impact on the wrinkling suppression effect, demonstrating the good inclusiveness of the formula. Regarding capacity retention, Examples 1-5 all maintained above 90.5%. As for the shedding rate, Examples 1-5 all maintained a low level of 0.62%-0.72%, but the shedding rates of Examples 2 (0.70%) and 4 (0.72%) were slightly higher than that of Example 1 (0.65%), indicating that when the edge current collector is thinned or the central adhesive content is reduced, the interfacial bonding strength will be affected to some extent. Regarding internal resistance, Examples 1-5 all maintained a low level of 28.5-29.3 mΩ.
[0089] Combining Examples 1, 6-8 and Tables 1 and 3, it can be seen that compared with Example 1, Examples 6-8 show that in Example 6, c was reduced from 1.00 to 0.90 (different binder systems); in Example 7, k was reduced from 1.20 to 0.80 (low expansion coefficient materials); and in Example 8, k was increased from 1.20 to 2.00 (high expansion coefficient materials). Under the above variable adjustments, the defect rate of Examples 6-8 remained at a low level of 2.7%-3.0%, which was not significantly different from Example 1 (2.8%). This indicates that the formula of this application has good adaptability to negative electrode materials with different binder systems and different expansion characteristics. By adjusting the c and k values in the formula, the influence of material performance differences on deformation matching can be automatically compensated. Regarding capacity retention, Examples 6-8 all maintained a relatively high level of 91.3%-91.5%, with Example 8's capacity retention (91.5%) being slightly lower than Example 1's (92.5%). This is related to the larger deformation stress generated by the high expansion coefficient material during cycling, but it is still significantly better than the comparative example. Regarding shedding rate, Examples 6-8 all maintained a relatively low level of 0.66%-0.73%, but Example 8's shedding rate (0.73%) was slightly higher than Example 1's (0.65%), indicating that the increased expansion coefficient places higher demands on interfacial bonding strength. Regarding internal resistance, there was little difference among the examples, all remaining between 28.7-29.2 mΩ.
[0090] Combining Examples 1, 9-13 and Tables 1 and 3, it can be seen that compared with Example 1, Examples 9-13 have different values. Example 9 increases λ from 1.50mm to 1.60mm, Example 10 decreases λ from 1.50mm to 1.20mm, Example 11 decreases λ from 1.50mm to 1.30mm, Example 12 increases λ from 1.50mm to 1.80mm, and Example 13 decreases λ from 1.50mm to 1.40mm. Correspondingly, the defect rate of Examples 9-13 remains at a low level of 2.6%-2.9%, which is not significantly different from Example 1 (2.8%). This indicates that the formula of this application has good robustness within the preferred range of edge region width, and can effectively suppress octopus wrinkling defects as long as the formula constraints are met. Regarding capacity retention, Examples 9-13 all maintained a retention rate between 90.5% and 92.1%, showing a slight decreasing trend with increasing λ. Specifically, Example 10 (λ=1.20mm) had a capacity retention rate of 90.7%, and Example 12 (λ=1.80mm) had a capacity retention rate of 92.1%. This may be related to changes in edge deformation distribution caused by variations in λ, but the capacity retention rates of all examples were significantly better than the comparative examples. Regarding the shedding rate, there was little difference among the examples, all remaining at a low level of 0.61%-0.74%, indicating that changes in edge width have a limited impact on interfacial bonding strength. Regarding internal resistance, all examples remained at a low level of 28.4-29.2mΩ with no significant difference, indicating that changes in edge width have a small impact on the cell's internal resistance.
[0091] Combining Examples 1, 14-17, and Tables 1-3, it can be seen that the defect rate and capacity retention rate of Examples 14 (positive and negative electrode thickness ratio of 0.6) and 15 (positive and negative electrode thickness ratio of 1.2) are basically equivalent to those of Example 1. This indicates that when the positive and negative electrode thickness ratio is within the range of 0.6-1.2, the expansion and contraction behaviors of the positive and negative electrodes can be coordinated and synchronized, resulting in a balanced overall cell deformation distribution. In contrast, Example 16 (positive and negative electrode thickness ratio of 0.5) shows an increased defect rate, decreased capacity retention rate, and increased shedding rate. This is because the excessively thin positive electrode results in insufficient structural rigidity, failing to provide effective constraint on the lithium intercalation expansion of the negative electrode, thus exacerbating the deformation instability of the negative electrode. Example 17 (positive and negative electrode thickness ratio of 1.4) also shows an increased defect rate, decreased capacity retention rate, and increased shedding rate. This is because the excessively thick positive electrode causes its own expansion and contraction behavior to become the dominant factor in cell deformation, disrupting the balanced deformation distribution at the edge of the negative electrode.
[0092] Based on Examples 1, 18-19 and Tables 1-3, it can be seen that in Example 18, the difference in width between the negative electrode and the positive electrode (2 mm) is greater than the width λ of the edge region (1.5 mm), and the edge of the positive electrode extends beyond the edge region of the negative electrode. In Example 19, the width λ of the edge region (4.5 mm) is greater than the difference in width between the separator and the negative electrode (4 mm), and the edge of the negative electrode extends beyond the coverage of the separator. The capacity retention rate of Examples 18 and 19 is lower than that of Example 1, the defect rate is higher than that of Example 1, and the shedding rate is higher than that of Example 1. This is because when the difference in width between the negative electrode and the positive electrode is greater than the width λ of the edge region, the positive electrode edge cannot fall into the negative electrode edge region. The high deformation region corresponding to the positive electrode edge cannot match the flexible buffer structure of the negative electrode edge, and the concentrated deformation load leads to aggravated edge deformation. When the width of the edge region is greater than the difference in width between the diaphragm and the negative electrode, the negative electrode edge exceeds the coverage of the diaphragm. The diaphragm cannot provide effective lateral constraint on the negative electrode edge, and the risk of edge deformation instability increases.
[0093] Furthermore, as shown in Table 3, the capacity retention rate of each embodiment after 1000 cycles remains above 90%, which is better than that of the comparative examples (88.1%-89.5%). This indicates that the technical solution of this application can effectively suppress the octopus wrinkling defect without adversely affecting the long-term cycle performance of the battery cell.
[0094] The above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application, but such modifications or substitutions are all within the scope of protection of this application.
Claims
1. A negative electrode sheet, characterized in that: It includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface along the thickness direction of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material and a binder; Along the width direction of the negative electrode sheet, the negative electrode sheet includes two edge regions located on both sides and a central region located between the two edge regions, and the sum of the widths of the central region and the two edge regions is equal to the width of the negative electrode sheet; The thickness of the negative electrode active material layer in the central region is the same as the thickness of the negative electrode active material layer in the edge region; With the thickness of the negative electrode current collector in the central region being h1 mm and the thickness of the negative electrode current collector in the edge region being h2 mm, h1 and h2 satisfy h1 > h2; Let λ mm be the width of any one of the edge regions of the negative electrode sheet; Let the coefficient of thermal expansion of the negative electrode active material be k, the performance constant of the binder be c, the mass percentage of the binder in the negative electrode active material layer in the central region be a1 wt%, and the mass percentage of the binder in the negative electrode active material layer in the edge region be a2 wt%. Let k, λ, c, h1, and a1 satisfy 1.3×(k×λ) / c≤1000×h1 / a1, and let k, λ, c, h2, and a2 satisfy 1000×h2 / a2≤28×(k×λ) / c.
2. The negative electrode sheet as described in claim 1, characterized in that: 1.3×(k×λ) / c≤1000×h1 / a1≤28×(k×λ) / c, and / or, 1.3×(k×λ) / c≤1000×h2 / a2≤28×(k×λ) / c.
3. The negative electrode sheet as described in claim 1, characterized in that: 1.5×(k×λ) / c≤1000×h1 / a1≤27×(k×λ) / c, and / or, 1.5×(k×λ) / c≤1000×h2 / a2≤27×(k×λ) / c.
4. The negative electrode sheet as described in claim 1, characterized in that: The value of h1 is 0.006-0.008, and / or the value of h2 is 0.004-0.
006.
5. The negative electrode sheet as described in claim 1, characterized in that: a1 and a2 satisfy at least one of the following conditions: (a) a1 = 0.5 - 3.0; (b) a² = 2.0 - 5.0; (c) a2 > a1.
6. The negative electrode sheet as described in claim 1, characterized in that: The k, the λ, and the c satisfy at least one of the following conditions: (1) The value of k is 5%-250%; (2) The value of λ is 1-5; (3) The value of c is 0.8-1.
2.
7. The negative electrode sheet as described in claim 1, characterized in that: The thickness of the negative electrode sheet is 50-200 μm.
8. A lithium battery, characterized in that: It includes a positive electrode, a separator, an electrolyte, and a negative electrode as described in any one of claims 1-7.
9. The lithium battery as described in claim 8, characterized in that: The difference in width between one side of the negative electrode and the positive electrode is less than the width of any of the edge regions, which is less than the difference in width between one side of the diaphragm and the negative electrode.
10. The lithium battery as described in claim 8, characterized in that: The ratio of the thickness of the positive electrode to the thickness of the negative electrode is 0.6-1.2.